Sister Grouping of Chimpanzees and Humans as Revealed by Genome-Wide Phylogenetic Analysis of Brain Gene Expression Profiles - Uddin, Monica; Wildman, Derek E.; Liu, Guozhen; Xu, Wenbo; Johnson, Robert M.; Hof, Patrick R.; Kapatos, Gregory; Grossman, Lawrence I.; Goodman, Morris (Proceedings of the National Academy of Sciences - PNAS, 2004)
Gene expression profiles from the anterior cingulate cortex (ACC) of human, chimpanzee, gorilla, and macaque samples provide clues about genetic regulatory changes in human and other catarrhine primate brains. The ACC, a cerebral neocortical region, has human-specific histological features. Physiologically, an individual's ACC displays increased activity during that individual's performance of cognitive tasks. Of ≈45,000 probe sets on microarray chips representing transcripts of all or most human genes, ≈16,000 were commonly detected in human ACC samples and comparable numbers, 14,000-15,000, in gorilla and chimpanzee ACC samples. Phylogenetic results obtained from gene expression profiles contradict the traditional expectation that the non-human African apes (i.e., chimpanzee and gorilla) should be more like each other than either should be like humans. Instead, the chimpanzee ACC profiles are more like the human than like the gorilla; these profiles demonstrate that chimpanzees are the sister group of humans. Moreover, for those unambiguous expression changes mapping to important biological processes and molecular functions that statistically are significantly represented in the data, the chimpanzee clade shows at least as much apparent regulatory evolution as does the human clade. Among important changes in the ancestry of both humans and chimpanzees, but to a greater extent in humans, are the up-regulated expression profiles of aerobic energy metabolism genes and neuronal function-related genes, suggesting that increased neuronal activity required increased supplies of energy.